Modifikasi Alat Ukur Tinggi Lutut untuk Pasien Bedrest - Agatha Widiyawati; Yohan Yuanta; Adinda Dwiana Sari (Puslitbang Sinergis Asa Professional, 2020)
Height measurement with special conditions such as total bedrest in hospitalized patients, the elderly, and people with disabilities can use knee height measurement devices. A knee height caliper is an anthropometric tool that is rarely used because it is large and made of wood or iron. This tool needs to be modified with the right accuracy level and makes it easy to measure knee height in bed rest patients. This study aims to know practicality's status in using and carrying tools and measuring knee height modification accuracy. The research design used was Research and Development (RnD) with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The first subject is the media expert on the media validation test using a validation assessment questionnaire. The media assessment is carried out at the implementation stage. The second subject is a nutritionist at dr. Soebandi Jember, as many as 11 nutritionists who are a small group. The percentage of the first stage media validation assessment was 74%, classified as good. The second stage was 70% classified as good, the third stage was 82% classified as very good, and the fourth stage was 100% classified as very good. The average result of the four stages of validation is 81.5% and classified as very good. The nutritionist's assessment results for the modification of the knee height device were 78.73%, and the media was classified as suitable for use. The study concludes that the modification of the knee height device is a tool designed using the 2015 Sketch Up software and from the results of the assessment of the knee height modification tool is suitable for use by health workers, especially nutritionists.